A COMPREHENSIVE RESEARCH ON MACHINE LEARNING AND BIG DATA ANALYSIS: ISSUES AND CHALLENGES - 1. Md. Attaur Rahman Sofi , 2. Prof. (Dr.) Santanu Sikdar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Machine Learning (ML) and Big Data are among the most transformative technologies of the 21st century. While ML empowers systems to learn from data and make decisions, Big Data provides massive, complex, and diverse datasets that serve as raw material for such learning. However, integrating ML with Big Data environments presents a unique set of challenges—including scalability, data quality, security, real-time processing, and model interpretability. This paper provides a comprehensive analysis of the technical and practical challenges associated with implementing ML on Big Data platforms. It further explores emerging technologies and strategies being employed to mitigate these issues.